2015
DOI: 10.1097/md.0000000000000940
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factors Associated With Response to Hepatitis B Vaccination in Patients With Inflammatory Bowel Disease

Abstract: It is recommended to investigate the serology of hepatitis B virus (HBV) and vaccinate seronegative patients at the time of diagnosis in inflammatory bowel diseases (IBD). This study aimed to investigate the efficacy of HBV vaccine and factors affecting the response.In this retrospective, observational study, HBV-seronegative IBD patients were administered 3 doses (at months 0, 1, and 6) recombinant 20 μg HbsAg. Patients’ demographics, IBD attributes, and treatment methods were investigated as the factors with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 31 publications
4
24
0
Order By: Relevance
“…Data from this study comparing the IBD population with a healthy population of the same age and geographical area confirm the significant loss of HBsAb titre among patients with IBD, with a greater tendency in CD than in UC (although the statistical significance was not achieved, most probably due to the sample size), as already reported in other studies [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Data from this study comparing the IBD population with a healthy population of the same age and geographical area confirm the significant loss of HBsAb titre among patients with IBD, with a greater tendency in CD than in UC (although the statistical significance was not achieved, most probably due to the sample size), as already reported in other studies [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 87%
“…Among yet identified risk factors for a missing seroprotection despite vaccination are diagnosis if CD, disease duration of more than 7 years, and an age at diagnosis of over 31 years [ 23 ], while conflicting data exist about the influence of immunosuppressive drugs on response to and on persistence of vaccine efficacy [ 15 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence on the immunogenicity and safety of vaccines in treated patients with IBD is still limited, as different immunomodulators can alter immune responses to vaccines [7,11,15]. According to some studies, patients with IBD had lower antibody responses after hepatitis B vaccination than the general population [7,20,21]. In other studies, IBD patients under treatment with infliximab and immunomodulatory therapy showed an impaired response to a single dose of trivalent inactivated influenza vaccine [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Gisbert et al also found worse vaccine response in patients using any immunosuppressant (20) . Cekic et al found that patients on corticosteroids and azathioprine in combination with anti-TNF had lower response to HBV vaccination (22) . Sempere et al also demonstrated worse response to vaccination in patients on corticosteroids therapy (11) .…”
Section: Discussionmentioning
confidence: 99%